The use of linseed and cottonseed to change the milk fatty acid profile in early lactation dairy goats - Nudda A.; Battacone G.; Fancellu S.; Carboni G.A.; Pulina G. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Renewed attention is being paid to the fatty acid (FA) composition of dairy products, because of the benefits of consumption of some long chain fatty acids on human health. The aim of this work was to evaluate the effects of dietary fat supplements on the FA composition of milk from goats in early lactation. Sixteen Sarda breed goats, fed 1.5 kg/day of concentrate and hay ad libitum, were divided into two groups: eight goats were supplemented with 32 g/d of fat from linseed (LIN) with a high C18:3 content, while the second group of animals received 32 g/d of fat from cottonseed (COT) with a high C18:2 content. The trial lasted 5 weeks: a 2-week preliminary period (PRE), a 2-week experimental period (EXP) and 1 week of recovery where the fat supplement was removed (REC). The FA profile of the goats' milk was determined by gas chromatography. The milk FA profile did not differ between PRE and REC periods. In the EXP period the milk FA profile was significantly influenced by the fat source. LIN significantly decreased the content of C14:0, C16:0 and the n-6/n-3 ratio more than COT did, whereas it increased the content of t11-C18:1, C18:3 n-3 and c9,t11 conjugated linoleic acid (CLA). As expected the t10,c12 CLA, the C20:5 n-3 (eicosapentaenoic acid, EPA) and C22:6 n-3 (docosahexaenoic acid (DHA) contents were low with both LIN and COT supplements, and did not differ with the two fat sources used. The results suggest that it may be possible to enhance the nutritional value of goat milk fat in early lactation by adding linseed to the diet.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)